Энерго- и ресурсосберегающие технологии в производстве поверхностно-активных веществ - Подустов, Михаил Алексеевич; Дзевочко, Александр Михайлович; Литвиненко, Евгения Игоревна; Бабиченко, Ю. А.; Черноног, Р. С. (НТУ "ХПИ", 2011)
The current state of the surface-active substances (SAS) in Ukraine. The basic energy- and resource-consuming features of SAS. Directions and how to increase energy and performance of the resource saving production.
Keywords: энергосбережение; ресурсосбережение; поверхностно-активные вещества; сульфатирующий агент; сульфатирование; очистка газовоздушного потока; органическое сырье; серная кислота; олеум; диоксид серы; массообмен